2007
DOI: 10.1007/s00586-007-0509-5
|View full text |Cite
|
Sign up to set email alerts
|

Vertebral endplate trauma induces disc cell apoptosis and promotes organ degeneration in vitro

Abstract: There is a major controversy whether spinal trauma with vertebral endplate fractures can result in posttraumatic disc degeneration. Intervertebral discs, which are adjacent to burst endplates, are frequently removed and an intercorporal spondylodesis is performed. In any case, the biological effects within the discs following endplate factures are poorly elucidated to date. The aim of our investigations was therefore to establish a novel disc/endplate trauma culture model to reproducibly induce endplate fractu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
72
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 102 publications
(76 citation statements)
references
References 51 publications
4
72
0
Order By: Relevance
“…In human as well as animal models of degenerative disc disease there are increased levels of inflammatory cytokine such as TNF-␣ and IL-1␤; our studies confirmed and extended these earlier findings (7,8,(23)(24)(25)(26)(27)(28). Likewise, in both mouse and human articular cartilage, cytokines and SDC4 expression is elevated during osteoarthritis (18).…”
Section: Discussionsupporting
confidence: 80%
“…In human as well as animal models of degenerative disc disease there are increased levels of inflammatory cytokine such as TNF-␣ and IL-1␤; our studies confirmed and extended these earlier findings (7,8,(23)(24)(25)(26)(27)(28). Likewise, in both mouse and human articular cartilage, cytokines and SDC4 expression is elevated during osteoarthritis (18).…”
Section: Discussionsupporting
confidence: 80%
“…Some studies have shown that intervertebral disc degeneration is inseparably linked with cartilaginous endplate degeneration [14,31] and Modic changes [47]. The cartilaginous endplate is indispensable to maintain the structural and functional integrity of local structures in the lower lumbar vertebral bodies [34].…”
Section: Discussionmentioning
confidence: 99%
“…The endplate cartilage was cut with ophthalmic scissors into pieces of approximately 1 mm 3 in size. Endplate cartilage pieces were collected aseptically, and chondrocytes were obtained by sequential digestion with Trypsin (Gibco) and Collagenase II (Gibco) as described previously (1 Application of cyclic strain. Chondrocytes (the second passage) were seeded on an elastic silicone membrane coated with collagen I (BioFlex, Flexcell International) at a density of 1x10 5 cells/well (diameter 35 mm) for culture.…”
Section: Methodsmentioning
confidence: 99%
“…However, the exact cause of this is unclear. Studies have found that disc degeneration begins in the cartilage endplate (1). Previous studies have shown that the process of cartilage disc degeneration in the vertebral endplate occurs with different degrees of calcification and that the degree of disc degeneration is positively correlated with calcification.…”
Section: Introductionmentioning
confidence: 99%